The Role of the Russian Orthodox Church in the Russia-Ukraine - Maforo, B. (BUSE, 2023)
The purpose of the study was to investigate the role of the Russian-Orthodox Church in the Russia-Ukraine war assessing whether it is promoting conflict or peace. The study used the functionalist theory of international relations and neo-classical realism. A qualitative research methodology was used together with a case study research design. Data was collected through in-depth interviews and document analysis. The data was collected from Orthodox Church Priests, Russian Community members domiciled in Zimbabwe, and political scientists. The findings of the study show that the ROC coexists with the Russian state. The ROC plays a key role in the geopolitics and foreign policy of the Russian state. The ROC sanitised the Russian invasion of Ukraine calling for the Russian victory in the war with Ukraine. Priests who sympathised with the Ukrainians and called for peace were defrocked by the ROC leadership. The global ecumenical fellowship of churches has ostracised the ROC over its support for the state. The ROC has influenced suspicion about the efficacy of the church in enabling peace among peace practitioners. The study recommended the ROC to be independent from the state so that it can objectively advise, applaud or critic the state. The Russian state must allow the ROC to be independent from the state. The ROC to consider standing for peace in a war situation because the greatest sanity and role of the church is the preservation of human life, as such the church must not be an instrument of destruction.
Keywords: Russian-Orthodox Church; Russia-Ukraine war; Conflict and Peace